Numerical Approach of Coupling Vibration Magneto-convection In Nanofluid - K Syham; M Elmir; R Mehdaoui (International Journal of Multiphysics, 2016)
The objective of our work is to visualize numerically the effect of coupling vibratory excitation and magnetic field on cooling an electronic component or a solar cell (originality of our study) in arid and semi-arid area. A square cavity of side H filled with Al2O3-water nanofluid where an electronic component is placed on the bottom horizontal wall is maintained at isothermal hot temperature Th. The top horizontal wall is maintained at a cold temperature Tc. The vertical walls are adiabatic. The equations describing the natural convection flow in the square cavity consist of mass conservation, momentum and energy. For the physical parameters of Al2O3-water nanofluid, we use the Brinkman and Wasp model. Transport equations are solved numerically by finite element method. The results are obtained for Rayleigh number Ra= 105, Hartmann numbers between 0 and 100 and vibratory excitation inclination angle between 0° and 90°. The external magnetic field inclination angle varies between 0° and 90° and the Rayleigh number ratio between 0 and 50.  Results are presented in the form of heat transfer flux ratio and maximum absolute value of stream function.